Cognitive and Functional Outcome among Hospitalized Intracerebral Haemorrhage Patients in West Java’s Top Referral Hospital - Ilham Bagas Setyawan; Paulus Anam Ong; M. Zafrullah Arifin (Althea Medical Journal, 2018)
Background: Stroke is the highest cause of disability in adults. Disability and cognitive function impairment cause dependency and decreasing quality of life. The objectives of this study was to describe the outcome of functional and cognitive function among intracerebral haemorrhage patients admitted to Dr. Hasan Sadikin General Hospital Bandung in 2013.Methods: This study was a quantitative descriptive study, conducted from October 2016 to August 2017. Data were collected retrospectively with total sampling method from medical records of intracerebral haemorrhage patients admitted to Dr. Hasan Sadikin General Hospital in 2013 assessed with the Montreal Cognitive Assessment-Indonesian Version (MoCA-INA) and Barthel Index. Patients with incomplete medical records , severe aphasia, severe sensoric-motoric impairment, and decreased consciousness were excluded in this study. Data were analyzed using Microsoft Office Excel 2010 and presented in percentage.Results: Out of the 26 subjects, 11 were men and 15 women , who were in the age range of 45–54 years (42.3%), with low education level (61.5%), and unemployed (61.5%) had the highest prevalence on subjects studied. Hypertension was the most common risk factor (78%). Most subjects had cognitive function impairment (69.2%) with delayed memory function as the most common impairment domain found (84.6%), followed by visuospatial/executive function (69.2%). Most subjects had a high score of dependence according to the Barthel test (61.5%).Conclusions: Two third of intracerebral haemorrhage patients have cognitive function impairment and functional dependence. Memory function is the most common impaired cognitive functional domain.